2021
DOI: 10.1038/s41598-021-97047-3
|View full text |Cite
|
Sign up to set email alerts
|

Positive relationship between seasonal Indo-Pacific Ocean wave power and SST

Abstract: The influence of increasing sea surface temperatures (SSTs), in response to greenhouse warming, on wave power (WP) remains uncertain. Here, seasonal relationships between SST anomalies and mean and extreme WP over the Indo-Pacific Ocean are examined. Overall, seasonal WP has significantly increased over much of the Pacific, Indian, and Southern Ocean by 1.21–3.10 kW/m dec−1 over 1979–2019. Contributions from wave characteristics, namely significant wave height (SWH) and peak wave period (PWP), to changes in WP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…A different study by Kaur et al. (2021) investigated the relationship between Indo‐Pacific Ocean wave power and SSTs using ERA5 data. The study also found an increase in wave power in the Pacific, with changes in wave period being the main contributor to the increase in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…A different study by Kaur et al. (2021) investigated the relationship between Indo‐Pacific Ocean wave power and SSTs using ERA5 data. The study also found an increase in wave power in the Pacific, with changes in wave period being the main contributor to the increase in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, TC has become a successful invader in the Western Atlantic probably due to its ability to withstand the effects of our changing climate as compared to its congener in the Indo-Pacific (TCP). Temperatures in the Western Atlantic are much cooler (season variation ranges from −2 • C to 30 • C) [65] than those in the Gulf of Mexico (20 • C to 28 • C) [66] or the Indo-Pacific, where annual temperatures remain above 28 • C [67]. Hence, the congener (TCP) used to stable seasonal temperatures seems less capable of adapting to wide-fluctuating temperatures experienced by TC.…”
Section: Discussionmentioning
confidence: 99%
“…The mean period, T01 and Te is related through the following relationship: Te=αT01, where, α depends on the spectral shape. We have considered α = 1 (Hagerman, 2001; Kaur et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The run‐up and coastal inundation can be more accurately evaluated with WP rather than using single wave parameter. It also represents variations in the wave climate more precisely than the other parameters (Kaur et al, 2021; Reguero et al, 2019). Reguero et al (2019) studied the long‐term seasonal and inter‐annual variations in global mean WP using model data of 61 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation